Teologi Inklusif Nurcholish Madjid: Harmonisasi Antara Keislaman, Keindonesiaan, dan Kemoderenan - Zainal Abidin (Bina Nusantara University, 2014)
This article is motivated by the phenomenon exists today, that Muslims are no longer perform properly inclusive theology. Religion is expected to bring mercy to all the worlds mission no longer demonstrate their role appropriately. Today most Muslims understand Islam as a doctrinal teachings, exclusive, and opposite with local wisdom and culture of Indonesia. Nurcholish Madjid gives a different idea in understanding Islam. For him, Islam is a modern and inclusive teaching of the other religions and cultures, and countries. Madjid is famous for his ideas about the reform of Islamic thought. According to him, Islam should be involved in the struggles modernistic based on the richness of traditional Islamic thought that have been established, once placed in the context of Indonesian-ness. Methodologically this study uses hermeneutic approach, and methods that is used in the search data is library research.